Reward-related neural activation during social media exposure in young women with non-suicidal self-injury: evidence for a continuum of severity in the reward network - Stella Nicolaou; Anna Julià; Daniela Otero; Carlos Schmidt; Juan Carlos Pascual; Joaquim Soler; Josep Marco-Pallarés; Daniel Vega (Translational Psychiatry)
Abstract Individuals with non-suicidal self-injury (NSSI) may be particularly vulnerable to social media exposure, yet the extent to which this vulnerability is linked to altered reward processing remains unclear. To address this gap, we investigated social media-related reward processing in NSSI by recruiting ninety-one young women, divided into three groups: a clinical group (NSSI with borderline personality disorder), a subclinical group (NSSI without co-occurring disorders), and a healthy control group. While undergoing functional magnetic resonance imaging (fMRI), participants received positive and negative comments on their own Instagram photos in a naturalistic task simulating real-life social media interactions. Clinical participants rated positive comments as less pleasant and negative comments as more unpleasant than controls. Coherently, they showed blunted activation in core reward regions such as the nucleus accumbens, caudate, and medial frontal cortex when receiving positive vs negative feedback. Subclinical participants reacted similarly to clinical participants to negative feedback but similarly to controls to positive feedback and presented intermediate activation in most regions, bridging the pattern observed in controls and patients. Results highlight reward system dysfunction as central to NSSI pathology, with both clinical and subclinical groups showing altered processing of social media-based feedback. Subclinical participants showed selective vulnerability to negative feedback, while clinical participants showed impaired sensitivity to both positive and negative feedback. These findings reflect a continuum of severity mapped on the reward system, highlighting potential intervention targets and emphasizing the need to address social media interactions in NSSI treatment.